Australian wine industry competitiveness: why so slow to emerge?1. (19th September 2018) - Anderson, Kym
Abstract : Despite favourable growing conditions, Australia's production or exports of wine did not become significant until the 1890s. Both grew in the 1920s, but only because of government support. Once that support was removed in the late 1940s, production plateaued and exports diminished: only two per cent of wine production was exported during 1975–1985. Yet over the next two decades, Australia's wine production quadrupled and the share exported rose to two‐thirds – before falling somewhat in the next 10 years. This paper explains why it took so long for Australia's production and competitive advantage in wine to emerge, why it took off spectacularly after the mid‐1980s and why it fell in the 10 years to 2016. It concludes that despite the recent downturn in the industry's fortunes, the country's international competitiveness is now firmly established and commensurate with its ideal wine‐growing climate, notwithstanding the likelihood of further boom‐slump cycles in the decades ahead.